Analysis of student scientific literacy using the socio-scientific issues (SSI) approach on reaction rate - Juli Yani; Neti Afrianis (Jurnal Pendidikan Kimia (JPKim), 2022)
This research at analyzing and knowing student science literacy after using Socio-Scientific Issues (SSI) approach on Reaction Rate lesson at the eleventh grade of MIPA 1 of State Senior High School 4 North Tambusai, Rokan Hulu. This research was conducted in the first semester in the Academic Year of 2019/2020. It was quantitative descriptive research. A purposive sampling technique was used in this research, and the samples were 32 students. The instrument was an essay test and it was supported by an unstructured interview. The data obtained then were analyzed descriptively. The results of analyzing the data showed, based on the data of essay test results, mean percentages of scientific literacy indicators: implementing the appropriate knowledge was 66.01% (good), identifying was 69.21% (good), explaining the implications of scientific knowledge for society was 80.94% (good), proposing ways to investigate scientific questions was 54.68% (enough), and drawing the right conclusion was 75.78% (good). It could be concluded that the achievement of student scientific literacy skills on the aspects of science competencies of Reaction Rate lesson at the eleventh grade of MIPA 1 overall was on good category.Keywords:Reaction Rate, Socio-scientific Issues approach, Student scientific literacy